2021
DOI: 10.1111/jace.17808
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously achieved high‐energy storage density and efficiency in (K,Na)NbO3‐based lead‐free ferroelectric films

Abstract: Dielectric capacitors have aroused extensive attentions as energy storage devices in the past few decades on account of their extremely fast charging-discharging process and consequent high power density, great voltage endurance, and low cost, 1,2 which gives them a great advantage in the application of pulsed power and power electronics such as hybrid electric vehicles, radar transmitters, frequency inverters, pacemakers, and electric weapon systems. [3][4][5] However, low-energy storage density and efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 63 publications
(146 reference statements)
1
26
0
Order By: Relevance
“…The rigid KNNLT-CZ5-Mn4 thin films were fabricated on Pt(111)/Ti/ SiO 2 /Si(100) substrates by a similar thermal process and showed a strong (100) texture in the previous work. 27 However, for the present flexible thin films, the (100) texture disappeared, notably. According to the nucleation theory, during the sol−gel process, the texture is influenced by inhomogeneous nucleation, which contents the factor f(θ) determined by the surface energies of film and substrate (θ refers to the wetting angle between the solution and substrates).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The rigid KNNLT-CZ5-Mn4 thin films were fabricated on Pt(111)/Ti/ SiO 2 /Si(100) substrates by a similar thermal process and showed a strong (100) texture in the previous work. 27 However, for the present flexible thin films, the (100) texture disappeared, notably. According to the nucleation theory, during the sol−gel process, the texture is influenced by inhomogeneous nucleation, which contents the factor f(θ) determined by the surface energies of film and substrate (θ refers to the wetting angle between the solution and substrates).…”
Section: Resultsmentioning
confidence: 64%
“…The breakdown electric fields of our flexible thin films are degraded if compared with those of their rigid counterparts with a larger thickness on Pt(111)/Ti/SiO 2 /Si(100) substrates. 27 However, compared with the formerly obtained flexible KNN thin films on polyimide by the growth-transfer technique, 36 the breakdown electric fields (E b ) exhibit great improvement. The E b becomes even comparable with several PZT-based flexible thin films on mica, or some BNT-based ones 34,35 that are represented by the high E b among various lead-free piezoelectric materials (Figure 2e, f and Table 1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanism of domain switching under an alternating current field of ferroelectrics has been widely investigated [ 9 ], e.g., the electric field influence on the elastic field [ 10 ], charged point defects [ 11 ], etc. However, the change of ferroelectric domains, e.g., phase states, domain pattern, etc., in a specific plane which is vertical to the direction of the external electric field during the loading and unloading process have rarely been reported, while the current studies have focused more on the domain evolution and properties variations in the same orientation with the electric field, i.e., the z-axis polarization component reverses with the electric field after a certain hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…This is detrimental to the electrical characterization of KNN-based materials and stunt its further development. Previous studies have demonstrated that chemical doping is an effective way to tune the electrical performance of KNN-based materials [21][22][23]. Kizaki et al have reported that the MnO 2 doping can effectively suppress the leakage current of KNN [24], and Huo et al have obtained high piezoelectric response (∼ 630 pC/N) in MnO 2 -doped KNN-based single crystal.…”
Section: Introductionmentioning
confidence: 99%